Tinjauan Peta Kawasan Keselamatan Operasi Penerbangan (KKOP) Bandara Ahmad Yani Semarang - Viradhea Gita R. L.; Sawitri Subiyanto; Arief Laila Nugraha (Departement Teknik Geodesi Universitas Diponegoro, 2014)
Airport Ahmad Yani is airport those are on Semarang, Central Java. Geographically, it located in co-ordinate 6 o 58 ’ 35 ” S 110 o 22 ’ 38 ” E. Airport Ahmad Yani’s location close to urban center that has a lot of tall building. Need to mark sense observation on tall object which potentially evoke troubles on flight activity (obstacle) those are on flight operations safety area especially airport vicinity area in order not to trouble the flight activity. The method that using in this final task research is method overlay identity by using of ArcGIS's software 9.3. Method overlay are methodic of spasial analisys that functioning result new spasial's data from minimal two data that becomes its entry. Overlay identity, part of method overlay that is utilized to save all information of all entry. After cartography utilizes ArcGIS's software 9.3 all through, then map is featured on Google Earth . The result of data processing are information about region which most turns in at Flight Operations Safety Area (KKOP) of Airport Ahmad Yani and height zona at any given area division. Thus, can be known about obstacle’s spread according to region and height zona on KKOP Airport Ahmad Yani. This research utilitarian to make development urban planning, monitoring the obstacles, and update of previous map. Keyword: Airport Ahmad Yani, KKOP, elevation, obstacle.